Design and Build an Eco Edu Tourism Application Using a Virtual Tour Guide in the Thematic Eco Enzyme Village, Padang City - Vadreas, Andrew Kurniawan; Purwasih, Ratih; Saputra, Heru; Stephane, Ilfa (Indonesian Journal of Community Services Cel, 2022)
The idea for the Eco Enzyme Thematic Village came about seeing the waste problem as a homework for urban areas. Based on the government decision of West Sumatra regulation number 286 of 2021 concerning 11 Locations and Themes for the Thematic Villages of Padang City in 2021 - 2024. One of the thematic villages is located in Andalas Village, namely the Eco Enzyme Thematic Village which was held by Waste Bank office unit at the Andalas. The pioneered of Eco Enzyme Thematic Village is Mr. Syaifudin Islami, M.Sc. This is one of community service activities aims to increase awareness and also educate the public to be willing to participate in waste management, especially in the Andalas Village area. In addition, to promote the Eco Enzyme Thematic Village area in waste processing. This community service offers a solution to promote Eco Enzyme Thematic Villages in Virtual Tour Guide Education (Pandu Wisata Edukasi) in the implementation and prospects of processing waste into Eco Enzymes. the application of virtual tour guide applies the SDLC (System Development Life Cycle) method using the waterfall model for system development and UML (Unifield Modeling Language) as a design tool. The expected results in using the latest technology, namely VR (Virtual Reality), can be a promotional and educational media that helps people know in real terms and seem to be involved in it.